Budgeting and Budgetary Institutions - Shah, Anwar (Washington, DC : World Bank, 2012)
Budgetary institutions have historically played a critical role in a gradual movement toward responsive, responsible, and accountable public governance in industrial countries. This paper includes the following headings: overview; a primer on budgeting and budgetary institutions; the budget and its coverage; capital budgets -- theory and practice; budget methods and practices; a primer on performance budgeting; accrual accounting in the public sector -- lessons for developing countries; activity-based cost management in the public sector; budget preparation and approval; budget execution; automating public financial management in developing countries; what would an ideal public finance management system look like; strengthening public expenditure management Africa -- criteria, priorities, and sequencing; budgeting in post-conflict countries; country case study -- Kenya; and country case study -- South Africa.